The Knowledge of Rehabilitation Professionals Concerning Fetal Alcohol Spectrum Disorders. Issue 1 (2nd January 2016) - Birch, Stephanie M.; Carpenter, Heidi A.; Marsh, Anna M.; McClung, Kimberly A.; Doll, Joy D.
ABSTRACT: The purpose of this study was to explore rehabilitation professionals' knowledge regarding signs and symptoms, prevention, and intervention of fetal alcohol spectrum disorders (FASD). Participants were 111 rehabilitation practitioners (e.g., occupational therapy, physical therapy, and speech-language pathology practitioners) recruited through email using a quantitative online survey design with purposive, snowball sampling. Results showed the majority of participants' demonstrated accurate knowledge of the signs and symptoms of FASD. Since professionals who received formal education on FASD reported significantly higher feelings of preparedness to identify children with FASD and manage/coordinate intervention plans, this study suggests rehabilitation professionals may be better prepared to treat individuals with FASD if they participate in formal training.